DYNAMIC RESPONSES OF FLOATING OFFSHORE PLATFORMS WITH LARGE HULLS - NG, NG CHENG YEE (2010)
Spar and semi-submersible are the most common types of floating offshore platforms used for deepwater operations. The spar consists of a hollow cylindrical deep-draft floating hull that provides buoyancy, with strake surrounding the hull to reduce vortex induce vibration and to held in place by mooring lines. To remain stable, it is important to maintain the centre of gravity always below the centre of buoyancy. The semi-submersible comprises of two horizontal water tight pontoons and number of column units that stand on the pontoons to provide support to the deck structure. It is held in place by mooring lines and dynamic positioning system. Both these types of platforms are made up of large-sized hull for providing buoyancy. As the ratio of the diameter of these structures to the wave length is above 0.2, the wave diffraction theory is the correct theory to be applied for the calculation of wave forces and wave damping, according to the literature. However, the application of diffraction theory, even linear one, is very much complicated and requires very costly commercial software. Hence, many research papers have reported results of dynamic analysis, using Morison equation for such cases, reasoning that for a considerable part of the frequency range, the ratio of diameter to wave length is still below 0.2. This is because of the ease of using Morison equation in programming and the possibility of incorporating the various non-linearity in the analysis. Yet, it has been established that the consultants are using only diffraction analysis for the analysis and design of such platforms. The aim of this study was to determine and compare the responses by both Morison equation and diffraction theory to the model test responses, and to suggest nonlinear multiple regression curves to estimate the structure responses. Model tests were conducted for spar and semi-submersible platform models in the wave tank at the Offshore Engineering Laboratory of Universiti Teknologi PETRONAS and the responses were measured. The respective prototypes were analyzed using a numerical Newmark Beta time domain integration method that was developed by using Matlab program. The platforms were designed as rigid bodies and three degree of freedom; surge, heave and pitch were considered. Linear wave theory and Morison equation were used for wave force determination in time domain analysis. A commercial software was employed to determine responses of the structures by Linear Wave Diffraction module. These results proved that the diffraction theory results were much closer to the actual model test results, thereby proving that using Morison equation for such platforms is not justified. Using the results of the diffraction analysis for a large number of platforms and conducting a non-linear multiple regression analysis, this thesis also suggests formulae to obtain suitable regression curves for predicting the diffraction responses of the spar and semi-submersible for any dimension and draft within the range suggested.